Insurance Contracts in the Agribusiness: A Global Overview of Agricultural Insurance with a Focus on Brazil - Fragoso, Rui (2022)
This study aims to give an overview on agricultural insurance, focusing the most common insurance contracts and identifying the main reasons associated with low general demand for agricultural insurances, namely in Brazil.The Indemnity Based Insurance and Revenue Insurance are the most common, but the Index Based Insurance contracts can avoid problems of adverse selection and moral hazard and the operational costs are lower. Like in European Union the subscription of agricultural insurances in Brazil is also low. It might be due to the low occurrence of weather advents with high adverse magnitude in the country. The development of agricultural insurances in this context requires new insurance products well adapted to the country conditions and highly subsided premiums by public funds.